KEBIJAKAN PEMBERIAN TAMBAHAN PERBAIKAN PENGHASILAN PEMERINTAH KABUPATEN KEDIRI - Anang Siswahyudi (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
This research aims to describe the implementation of additional refinement income policy in Kediri Regency. The result shows that: 1. The process of compiling policy runs in a planned and system according to the stage of policy formulation. In identification issues of administration, the wording has been based on strategic topics such as a). The condition of the reality of the performance of employees tends to be lower, b). The level of welfare and income disparities rate for employees. In taking the model or the alternative selection of policy is an interracial process between bureaucracy elite actors in the district government of Kediri which influences the form of additional refinement income policy determination 2). The type of other refinement income policy of Kediri district government is acquired through three variables: position, presence, and employee performance; 3). In the implementation of additional refinement, income policy has been supported by the system, and the existing plan in the operation of finger online towards employee attendance and performance variables through the instrument of performance achievement is made at the end of the year. In the implementation of the other variables based on positions. In the application of the three variables seem less effective in terms of performance variables because it does not reflect the performance of employees every day, while in the acquisition of additional refinement income policy is still perceived disparities between staff employees with the structural employees consequently have not been able to improve performance significantly to the lower level employees.